Failure analysis of historic vertical breakwaters, part 2: Alderney, Guernsey and Dover, UK. Issue 4 (16th November 2020) - Allsop, Nigel William Henry; Bruce, Tom
Abstract : Many historic breakwaters failed early in their life, leaving little information by which to analyse or understand their failures. As part of a wider analysis of 'old breakwaters', the first author has analysed the 'stability' of example vertical breakwaters using analytical methods developed over the past 20 years. This analysis is illustrated in this and the companion paper by three case studies: Wick (designed by Thomas Stevenson, failed 1870–1877); Alderney (damaged even during construction, lost its outer length 1865–1889); and Dover (still shows high stability after 110 years). In each of these case studies, representative cross-sections have been derived from historical records, as have the approach bathymetry. Representative wave conditions are transformed to the breakwater toes, including depth-limiting and impulsive breaking effects. Empirical formulae developed during and since the PROVERBS (Probabilistic Design Tools for Vertical Breakwaters) project have been used to explore incidence of wave impact loads, the main momentum loads and impulsive loads. Factors of safety against sliding and/or overturning have been determined for each example over a range of representative wave conditions.